Uma forma de apresentação da interpretação geométrica do logaritmo natural e estudo de algumas de suas propriedades - Felix, Rodrigo Aécio (2013)
The objective of this work is to propose a sequence for teaching motivating and interesting knowledge construction logarithm. The vast majority of textbooks adopted by school teachers addresses this issue in the traditional way, with a definition (definition of logarithm as an exponent) less suitable for the construction of this significant concept, properties and seen by most students as nonsensical rules, imposed and often unproven. Besides this the mathematical demonstrations are increasingly less practiced with students due to poor posture currently adopted by many teachers, whose reasons are: teachers does not dominate them, they believe are not necessary or that students are unable to assimilate them. This attitude results in traditional classes whose results are disinterested and unmotivated students, contributing greatly to the current scenario of the schools, where many of them finish high school without even build this important mathematical concept in their minds. The teaching sequence was developed and applied according to the concepts of Engineering Curriculum, using computer programs Geogebra 4.2, Excel 2010 and Windows Scientific Calculator in a proposed six classes: the first aimed to present the project, highlighting the importance of logarithms and its applications, the latter performing an activity where students use computer programs to observe and perceive the geometric interpretation of the natural logarithm, and other classes where students performing activities, also through computer programs, should realize and conjecture properties logarithms. To achieve a good result, the three classes immediately following the implementation of the activities were aimed at socializing the results and demonstrations of the mathematical properties of logarithms, conjectured or not the students in this project. To finish, we applied a diagnostic assessment, in order to measure the efficiency of this project, that is, if he really contributed to the building of effective knowledge logarithmic in students involved.